2020
DOI: 10.1177/2050312120922659
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient satisfaction with pharmacy service and associated factors in public hospitals, Eastern Ethiopia

Abstract: Background: A comprehensive understanding of the extent of patient satisfaction and its determinants are crucial in improving the quality of service. Hence, this research was designed to measure patient satisfaction with pharmacy service. Methods: A cross-sectional study was conducted among 422 patients to assess satisfaction with pharmacy service in public hospitals located in Eastern Ethiopia from September to January 2018. Data were collected through an exit interview using structured questionnaires. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 36 publications
4
30
4
Order By: Relevance
“…Our finding is in line with the availability of 76% of drugs in a general hospital in Ethiopia [ 23 ]; however, it is lower than a national report of 86.4% proportional availability of prescribed medicines to be dispensed in the APTS implemented hospital pharmacies in 2016 [ 16 ]. In contrast to our finding the lower proportion of clients were receiving all medications prescribed in the hospitals of Eastern Ethiopia 35% [ 10 ] and Dessie public hospital 56% [ 8 ]. This variation may be due to the differences in methods of measuring the proportional availability of prescribed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding is in line with the availability of 76% of drugs in a general hospital in Ethiopia [ 23 ]; however, it is lower than a national report of 86.4% proportional availability of prescribed medicines to be dispensed in the APTS implemented hospital pharmacies in 2016 [ 16 ]. In contrast to our finding the lower proportion of clients were receiving all medications prescribed in the hospitals of Eastern Ethiopia 35% [ 10 ] and Dessie public hospital 56% [ 8 ]. This variation may be due to the differences in methods of measuring the proportional availability of prescribed.…”
Section: Discussioncontrasting
confidence: 99%
“…In Ethiopia, institution-based studies found slightly higher than 50% overall patient satisfaction towards outpatient pharmacy services which is generally low [ 2 , 3 , 8 10 ]. The patients score higher satisfaction with the promptness of prescription medication service [ 2 ], and professionalism of the pharmacy staff [ 3 ] but lower on the information provided on storage, and possible side effects of medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is slightly lower than a study conducted at Dessie Town Hospitals (59.4%). 34 However, it is higher than study carried out at Yekatit 12 Medical College Hospital (47%), 35 Gondar University Referral Hospital (49.6%) 36 and the public hospitals of western and eastern Hararghe zone (6.19%) 37 in Ethiopia. This variation could be related to the difference in scope of the study, in which the current study assessed the PC in terms of pharmacist-direct contact with patients, clinical pharmacy services while comparative studies were based on usual pharmacy service, concentrating on the out-patient pharmacy services.…”
Section: Discussionmentioning
confidence: 72%
“…5,13 In Ethiopia, patient dissatisfaction with the amount and quality of medicines information has often been reported. 14,15 Beyond that report, no further results have been published about the readability, patients' perception, and understanding of the medicine information materials in Ethiopia. Therefore, this study aimed to assess the readability, patients' perception, and understanding of the medicine information materials (MIMs) in Tikur Anbessa Specialized Hospital (TASH), Addis Ababa, Ethiopia.…”
Section: Introductionmentioning
confidence: 92%